30 Jahre Stiftungen der LTG : Lufttechnische GmbH Stuttgart. - Beye, Peter; Keppler, Peter; Reuter, Edzard; LTG Lufttechnische GmbH, Stuttgart (Stuttgart : Staatsgalerie Stuttgart, 1990)
Munch, Edvard ; Baumeister, Willi ; Masson, Andre ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Michaux, Henri ; Mathieu, Georges ; Giacometti, Alberto ; Jenkins, Paul ; Louis, Morris ; Segal, George ; Christo ; Klein, Yves ; Tinguely, Jean ; Roehr, Peter ; Rotella, Mimmo ; Raysse, Martial ; Blais, Jean-Charles
biografie, bibliografie
30 Jahre Stiftungen der LTG Lufttechnische GmbH Stuttgart, Staatsgalerie Stuttgart, 27. Januar bis 4. März 1990
German
kunstcatalogus